You like it darker : stories [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2024)
These 12 stories, about fate, mortality, luck, and the folds in reality where anything can happen, are as rich and riveting as King's novels, both weighty in theme and a huge pleasure to read. King writes to feel 'the exhilartion of leaving ordinary day-to-day life behind,' and in You Like It Darker, listeners will feel that exhilaration too, again and again. "Two Talented Bastids explores the long-hidden secret of how the eponymous gentlemen got their skills. In Danny Coughlin's Bad Dream, a brief and unprecedented psychic flash upends dozens of lives, Danny's most catastrophically. In Rattlesnakes, a sequel to Cujo, a grieving widower travels to Florida for respite and instead receives an unexpected inheritance, with major strings attached. In The Dreamers, a taciturn Vietnam vet answers a job ad and learns that there are some corners of the universe best left unexplored. The Answer Man asks if prescience is good luck or bad and reminds us that a life marked by unbearable tragedy can still be meaningful.